Peningkatan Peluang Bisnis Strategi Industri Migas Terhadap Pengaruh Pandemi Covid-19 Di Indonesia - Edy Soesanto; Aly Rasyid; Bobby Devagan (Department of Petroleum Engineering, 2022)
The oil as well as fuel market participates in an essential function in the Indonesian economic climate, as an income source APBN as well as a resource of power (particularly gas) towards steer different industries of lifestyle throughout Indonesia. Limitations on individual motion have actually resulted in a straight decrease popular for gas. Along with reducing usage, Covid-19 likewise has actually an effect on reducing oil as well as fuel costs as well as manufacturing, consisting of ceasing upstream tasks as well as decreasing fine-tuning tasks. Within this particular examine, monitorings were actually made from all of upstream oil as well as fuel company tasks in Indonesia particularly, since the effect of the Covid-19 pandemic consisted of the effect of worldwide problems overall, to ensure that healing initiatives could be created in addition to recommendations for handling problems that might intensify. The outcomes of this particular examine end that the avoidance of the effect of Covid-19 for the upstream oil as well as fuel company should be actually performed comprehensively as well as includes all of stakeholders, to ensure that the oil as well as fuel market can easily remain to make it through amidst the direct visibility of the Covid-19 pandemic. Reference: Dito Aditia Darma, et all, Dampak Pandemi Covid-19 Terhadap Perekonomian Indonesia, Jurnal Benefita 212-224, Juli 2020. Nugroho, H. (2018a). Pemikiran Mengenai Pembangunan Industri Gas Bumi Indonesia. Depok : Institute of Development & Energy Economics. Nugroho, H. (2018b). Reserves and security of our energy supply, dalam Thoughts on Indonesian Energy Issues & Policies. Jakarta : Bappenas Nur Laila Widyastuti, et all, Dampak Covid-19 terhadap Industri Minyak dan Gas Bumi: Rekomendasi Kebijakan untuk Indonesia, The Indonesian Journal of Development Planning Volume IV No. 2 – Juni 2020. Republik Indonesia, (2020). Anggaran Pendapatan & Belanja Negara https://www.kemenkeu.go.id/informasi-publik/uu-apbn-dan-notakeuangan/, diakses pada tanggal 10 September 2020. SKKMIGAS, https://www.skkmigas.go.id/publikasi/infographic, di akses pada tanggal 20 Oktober 2020. Tirto.id Website, Update Corona Indonesia April 2020, https://tirto.id/update-corona-indonesia-21-april-2020-data-covid-19-dunia-terkini-ePYZ, diakses tanggal 21 April 2020.